2017
DOI: 10.22256/pubvet.v11n12.1285-1292
|View full text |Cite
|
Sign up to set email alerts
|

Incubação de ovos e desenvolvimento pós-natal de Kinosternon scorpioides (Linnaeus, 1766) (Testudines, Kinosternidae) cativos

Abstract: RESUMO. Este trabalho teve como objetivo descrever a incubação artificial de ovos deKinosternon scorpioides (Linnaeus, 1766) e verificar se houve influência da temperatura e umidade sobre o peso e o tamanho dos neonatos em cativeiro. Foram coletados 51 ovos no recinto de reprodução do Criadouro Científico do Projeto Bio-Fauna -ISARH/UFRA, Belém, Pará, os quais foram mantidos em seis incubadoras sob permanente controle térmico e hídrico, com os valores de temperatura e umidade constantes, fixados em 29,6 ºC e 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…K. scorpioides features diapause and embryonic aestivation (Ewert, 1985, 1991), which directly affects incubation time (Ewert, 1985; Ewert & Wilson, 1996; Rafferty & Reina, 2012). Here it is shown that the incubation period occurs at 129.50 ± 21.73 days (Braga, 2019), similar to several studies carried out in northern Brazil (Costa et al, 2017; Guimarães, Silva, & Palha, 2017). The long Stage 26 (prehatch), observed during 60 days of incubation, demonstrates the presence of embryonic aestivation (Braga, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…K. scorpioides features diapause and embryonic aestivation (Ewert, 1985, 1991), which directly affects incubation time (Ewert, 1985; Ewert & Wilson, 1996; Rafferty & Reina, 2012). Here it is shown that the incubation period occurs at 129.50 ± 21.73 days (Braga, 2019), similar to several studies carried out in northern Brazil (Costa et al, 2017; Guimarães, Silva, & Palha, 2017). The long Stage 26 (prehatch), observed during 60 days of incubation, demonstrates the presence of embryonic aestivation (Braga, 2019).…”
Section: Discussionsupporting
confidence: 89%